PENGARUH STRESS KERJA, KEPUASAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR DESA SANUR - Gregorius Paulus Tahu; Anak Agung Dian Padma Dewi; I Gusti Ngurah Bagus Gunadi (EMAS, 2024)
People's Credit Bank (BPR) is a bank that carries out business activities conventionally or based on sharia principles. PT. BPR Sanur Village is a business engaged in banking services, in the form of a limited liability company (PT) that accepts deposits in the form of deposits, savings, credits, and other forms that are perceived equally and provide financial service products in the form of loans or credits. The purpose of this study is to determine the Effect of Work Stress, Job Satisfaction, and Work Motivation on Employee Performance at PT. BPR Sanur Village. The object of research used in this study is the Effect of Work Stress, Job Satisfaction, and Work Motivation on Employee Performance at PT. BPR Sanur Village. This research took the object at PT. BPR Sanur Village. The sampling technique used in this study used a saturated sample or census technique, which was a total of 46 respondents. The data analysis method used in this study is using multiple linear regression analysis techniques, correlation analysis tests, determination coefficient tests, and t statistical tests. Based on the results of the research that has been done, the following conclusions can be drawn: (1) Work stress has a negative and significant effect on employee performance, this is evidenced by the t-count value of - 0.237 with a significance level of 0.043 (0.043 < 0.05), (2) Job satisfaction has a positive and significant effect on employee performance as evidenced by the t-count value of 0.383 with a significance level of 0.001 (0.001 < 0.05), and (3) Work motivation has a positive and significant effect on employee performance as evidenced by the t-count value of 0.333 with a significance level of 0.005 (0.005 < 0.05).